The Effect of Pleurotus sajor-caju (PSC) Addition on the Nutritional Composition and Sensory Properties of Poultry-Based Patty - Wan Rosli, W. I.; Solihah, M.A.; Nik Fakurudin,, N. A.; Aishah, M. S.; Mohsin, S. S. J. (World Academy of Science, Engineering and Technology (WASET), 2011)
The nutrient composition and sensory properties of poultry-based patties (PBPs) incorporated with various levels of grey oyster mushroom (Pleurotus sajor-caju, PSC) were studied. The PBPs were formulated with either 0%, 25% or 50% of fresh ground PSC. Results show poultry patty formulated with 25% PSC had protein content of 17.46% lower than the control patty which had 18.13% but it was not significant. Meanwhile, both cooked poultry patties containing 25% and 50% PSC significantly recorded lower concentration of fat at 10.67% and 7.15%, respectively. On the other hand, poultry patty added with 50% ground PSC shows the highest concentration of total dietary fibre (TDF) of 4.90 g/100g compared to poultry patty containing 25% of mushroom (3.40 g/100g) and to the control (1.90g/100g). In addition, patty incorporated with 25% PSC had moisture content of 57.91% which is significantly lower than patty formulated with 50% which had moisture of 61.80%. In the sensory evaluation, there were no differences recorded in all sensory attributes of PSC-based patties judged by untrained panelists. In conclusion, the addition of PSC to replace poultry meat can be recommended for the purpose of lowering production cost, enhancing nutritional composition and maintaining the acceptability of poultry patties.